Individual Matrixes of Values As Basis for Social Group Members’ Behavior Correction - S. S. Frolov (Управление)
Management on values represents very perspective area of activity concerning the human relations management. Consequently, in this paper the author analyzes individual matrixes of values as a basis for social group members’ behavior management. At the same time questions related to social norms correction within ordered series of cultural values are considered.